The influence of OsAUX1 on root system architecture and phosphorus uptake in rice (Oryza sativa) - Zappala, Susan Christine (2014)
Rice (Oryza sativa L.) provides up to 50% of the total calories consumed in countries such as India, Madagascar and Nigeria. As a crop, rice can require significant fertiliser inputs to maintain the required yields. Additionally, climate change has increased the need for rice varieties with improved drought resistance, tolerance to pests and more efficient acquisition of nutrients from soil. One major fertiliser input for rice is phosphate; reducing phosphorus (P) fertiliser use would have environmental and economic implications. Root traits linked to P acquisition in crops include shallow root angle, lateral root proliferation and increases in root hair length and density. Two T-DNA knockout alleles with reduced gravitropic response, Osaux1-1 and Osaux1-2, were used to investigate the influence of shallow root angle on P uptake. OsAUX1 is a rice ortholog for the Arabidopsis thaliana gene AUX1, which controls lateral root growth and gravitropic response. The wildtype and mutant rice plants were grown in soil and non-destructively imaged using X-ray micro Computed Tomography (X-ray CT). In Chapter Three, visualisation of rice roots in soil using X-ray CT was optimised by determining the ideal soil moisture content that would produce the best images. Water in soils has a similar X- ray attenuation density to that of plant roots and can influence segmentation of roots from soil in X-ray CT images. It was found that soil at nominal field capacity (ca. 3 days of drainage) produced the best contrast between soil fractions (organic matter, minerals and pore space) and root material. In Chapter Four, the impact of X-ray dose on root growth was quantified because the experimental design included repeated scanning of the same sample (Chapter Five). It was found that even under repeated scanning, the X-ray doses involved in this work (ca. 15 Gy per sample) did not significantly affect the root architecture and overall plant growth in rice cultivars used. In Chapter Five, Osaux1-1 and Osaux1-2 retained the agravitropic phenotype that was observed on agar-based systems when plants were grown in loamy sand soil. However, when subject to various soil P concentrations and distributions (Chapter Six), Osaux1-1 had similar gravitropic response and P uptake as wildtype. It was unclear what role gravitropism and topsoil foraging played in P uptake for these rice cultivars, if any. OsAUX1 could be linked to P uptake as well as responses to soil P concentration and distribution. Under uniformly low soil P wildtype had a shallower root system distribution than Osaux1-1. Of most interest were the results when sufficient soil P was sequestered to the top 4 cm of the soil column and low P was maintained in the bottom 6 cm. Under these conditions, wildtype took up more overall P, had almost twice the biomass, twice the total root length and twice the surface area when compared to Osaux1-1. This provides evidence that OsAUX1 can be linked to adaptation to P stress and distribution of P in soil through control of fine root characteristics and not necessarily its impact on gravitropic response. Chapter Seven describes the investigation into the impact of OsAUX1 on sub-architectural effects of the root system that could influence P uptake. It was determined that OsAUX1 was involved in root hair density and elongation under varying P availability for agar grown plants. In comparison to wildtype, Osaux1-1 had significant variation in root hair phenotype that seemed unrelated to a P stress response. In flooded environments, root hairs influence the potential for root:soil contact that is integral to P uptake in rice paddies which have reduced soil conditions and mass water flow that can transport plant available soluble P. This reinforces the potential for an interaction between OsAUX1 and P uptake in paddy rice.